2016
DOI: 10.1167/iovs.iovs-15-18677
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofPGFas a New Gene for Neovascular Age-Related Macular Degeneration in a Chinese Population

Abstract: PURPOSE.To determine the associations of the VEGFA, VEGFB, and placental growth factor (PGF) genes with neovascular age-related macular degeneration (nAMD) and polypoidal choroidal vasculopathy (PCV).METHODS. Seven single-nucleotide polymorphisms (SNPs) in VEGFA, three SNPs in VEGFB, and five SNPs in PGF were genotyped in 1722 unrelated Chinese participants, including a Hong Kong cohort of 214 nAMD patients, 236 PCV patients, and 365 controls, and an independent Shantou cohort of 189 nAMD patients, 187 PCV pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…1 Clinical investigations have shown that the expressions of PIGF, VEGF, and endocan are upregulated in vitreous fluid from patients with proliferative diabetic retinopathy. 25,26 Based on our results, inhibition of endocan caused a decrease in VEGF, PIGF and their receptors in the OIR and CNV models, suggesting that the blockade of endocan can modulate angiogenic activities in pathologic NV progression by interacting with VEGF family members. Our results were consistent with previous reports showing that VEGF signaling was reduced in the absence of endocan in the early postnatal mouse retina.…”
Section: Discussionmentioning
confidence: 68%
“…1 Clinical investigations have shown that the expressions of PIGF, VEGF, and endocan are upregulated in vitreous fluid from patients with proliferative diabetic retinopathy. 25,26 Based on our results, inhibition of endocan caused a decrease in VEGF, PIGF and their receptors in the OIR and CNV models, suggesting that the blockade of endocan can modulate angiogenic activities in pathologic NV progression by interacting with VEGF family members. Our results were consistent with previous reports showing that VEGF signaling was reduced in the absence of endocan in the early postnatal mouse retina.…”
Section: Discussionmentioning
confidence: 68%
“…24 A P value less than 0.0012 (0.05/42, where 42 is the pairs of interaction) defined a significantly statistical interaction. After identifying a significant interaction between ANGPT2 rs13269021 and CFH rs800292, the study subjects were stratified by using dominant and recessive models of the risk G allele of ANGPT2 rs13269021.…”
Section: Discussionmentioning
confidence: 99%
“…We were most interested in the two most commonly occurring SNPs within the PGF gene, rs2268614 and the rs2268615, owing to their previously described association with plasma levels of PGF 9 and the association with genetic susceptibility to angiogenesis-driven disease. 8 Genotyping was successfully performed for Genotyping of the vascular endothelial growth factor A single nucleotide polymorphisms À460 (rs833061) and +405 (rs2010963)…”
Section: Dna Extraction From Bloodmentioning
confidence: 99%
“…7 A significant association between the haploblock-tagging SNPs rs2286614 and rs2268615 and neovascular age-related macular degeneration has been reported in two Chinese cohorts, suggesting a role for PGF as a susceptibility gene in a disease with a putative angiogenic basis. 8 Furthermore, the rs2268614 SNP has been associated with plasma levels of PGF in two independent European populations. 9 Little is known about what regulates PGF gene expression, although several studies have implicated VEGFA as a key regulatory factor.…”
Section: Introductionmentioning
confidence: 99%